Thymoquinone and Costunolide Induce Apoptosis of Both Proliferative and Doxorubicin-Induced-Senescent Colon and Breast Cancer Cells. (September 2021) - El-Far, Ali H; Godugu, Kavitha; Noreldin, Ahmed E.; Saddiq, Amna A.; Almaghrabi, Omar A.; Al Jaouni, Soad K.; Mousa, Shaker A.
Doxorubicin (Dox) induces senescence in numerous cancer cell types, but these senescent cancer cells relapse again if they are not eliminated. On this principle, we investigated the apoptotic effect of thymoquinone (TQ), the active ingredient of Nigella sativa seeds and costunolide (COS), the active ingredient of Costus speciosus, on the senescent colon (Sen-HCT116) and senescent breast (Sen-MCF7) cancer cell lines in reference to their corresponding proliferative cells to rapidly eliminate the senescent cancer cells. The senescence markers of Sen-HCT116 and Sen-MCF7 were determined by a significant decrease in bromodeoxyuridine (BrdU) incorporation and significant increases in SA-β-gal, p53, and p21 levels. Then proliferative, Sen-HCT116, and Sen-MCF7 cells were subjected to either TQ (50 µM) or COS (30 µM), the Bcl2-associated X protein (Bax), B-cell lymphoma 2 (Bcl2), caspase 3 mRNA expression and its activity were established. Results revealed that TQ significantly increased the Bax/Bcl2 ratio in HCT116 + Dox5 + TQ, MCF7 + TQ, and MCF7 + Dox5 + TQ compared with their corresponding controls. COS significantly increased the Bax/Bcl2 ratio in HCT116 + Dox5 + TQ and MCF7 + Dox5 + TQ compared with their related controls. Also, TQ and COS were significantly increased caspase 3 activity and cell proliferation of Sen-HCT116 and Sen-MCF7. The data revealed a higher sensitivity of senescent cells to TQ or COS than their corresponding proliferative cells.